2022
DOI: 10.1177/14752409221090440
|View full text |Cite
|
Sign up to set email alerts
|

The PISA performance gap between national and expatriate students in the United Arab Emirates

Abstract: In most education systems, students with an immigrant background perform worse academically than do native students. However, in the United Arab Emirates (UAE) differences emerge in the opposite direction and the national-expatriate gap in academic performance is equivalent to almost three years of schooling. This gap is a concern in the UAE, where national students mainly attend public schools while expatriates mostly attend private schools. In this study, to investigate the performance gap between national a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 75 publications
0
16
0
1
Order By: Relevance
“…School factors that produce low academic performance may also fuel mental health concerns, especially as one drives the other (Agnafors et al, 2021 ; Deighton et al, 2018 ; Pagerols et al, 2022 ; Riglin et al, 2014 ). Alternatively, issues identified in UAE public schools, i.e., non-national teachers, low status of teaching, low teacher wellbeing, few resources, and little parent support (Marquez et al, 2022b ) may contribute.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…School factors that produce low academic performance may also fuel mental health concerns, especially as one drives the other (Agnafors et al, 2021 ; Deighton et al, 2018 ; Pagerols et al, 2022 ; Riglin et al, 2014 ). Alternatively, issues identified in UAE public schools, i.e., non-national teachers, low status of teaching, low teacher wellbeing, few resources, and little parent support (Marquez et al, 2022b ) may contribute.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Buckner ( 2018 ) found that low-income Emirati nationals had worse academic performance on the 2015 and 2018 PISA exams (OECD, 2019 ) than their higher income peers, with the influence of SES on academic achievement stronger in the UAE than elsewhere. In addition to the three-year private–public academic performance gap (Marquez et al, 2022a , b , c ), there is also a gender gap. Nationally, girls have outperformed boys in all PISA subjects since 2012 and this gap is also larger than anywhere else (OECD, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although research on drivers of student wellbeing in the UAE is scarce, a national study by Marquez et al (2022) provides valuable information. The authors found geographic, socio-demographic, and school-type differences in adolescent wellbeing and these varied across distinct wellbeing domains.…”
Section: Students' Wellbeing In the Uaementioning
confidence: 99%
“…The issues identified in the analysis must be addressed by schools and other stakeholders. Doing so may help promote student wellbeing and more importantly, reduce wellbeing inequalities, including socio-demographic (e.g., SES) and school type inequalities, both of which are large in the UAE (Marquez et al, 2022).…”
Section: Findings and Policy Recommendationsmentioning
confidence: 99%
“…Dolayısıyla PISA, dünyada ve ülkemiz eğitim otoriteleri tarafından da önemsenmekte, eğitim sistemimiz dinamikleri sık sık PISA ile karşılaştırılmaktadır. Örneğin güncel alanyazın incelendiğinde; ülkeler arası akademik başarı bağlamında karşılaştırmaların yapıldığı (Boman, 2022;Üstün, Cansız, Özdemir ve Cansız, 2022;Marquez, Lambert, Ridge ve Walker, 2022;Erdoğdu, 2022), farklı uygulamaların PISA performansına etkilerinin araştırıldığı (Navarro-Martinez ve Peña-Acuña, 2022; Jerrim, Lopez-Agudo ve Marcenaro-Gutierrez, 2022;Dong ve Kula, 2022;Liu ve Wang, 2022), öğrencilere ve eğitim sistemlerine ilişkin bazı niteliklerin PISA performanslarına etkisinin araştırıldığı (Qian ve Lau, 2022;Khine, Fraser, Afari ve Liu, 2022;Yang, Fan ve Chen, 2022;İnci ve Kaya, 2022;Kaya, Eryilmaz ve Yüksel, 2022;Finch ve Finch, 2022) çalışmalara sıklıkla rastlanmaktadır. Ancak yapılan karşılaştırmalar, görüldüğü üzere çoğunlukla test sonuçları üzerinden olmakta ve akademik başarıya odaklanmaktadır.…”
Section: Introductionunclassified